To, co idealne, i to, co faktyczne - analiza zmiennych hipotetycznych i faktycznych aktów wychowania - Jarosław Gara (Nicolaus Copernicus University in Toruń, 2009)
Understanding something is a result of the ability to ask certain questions, as they always make everything understandable. Therefore the epistemological and methodological starting point for the discussion of the problems presented here is the following question: which aspects should be taken into account as far as the analysis of the acts of education is concerned. Upbringing is never something homogeneous because educational influences always accumulate, sum up and are a requisite of each other. Pedagogical influences also concern different spheres of human life and that is why one can also talk about narrow or wide range of such influences. It should also be added that everything that happens in human life is connected with two basic dimensions, i.e. time and space. Definite acts of education are therefore determined by some specific proprieties of time and space of upbringing. In this way education can be discussed within these specific contexts. What is more, there is no way to understand the aims and tasks of upbringing without getting to know these contexts.